2022
DOI: 10.1177/02698811221142568
|View full text |Cite
|
Sign up to set email alerts
|

Effects of modafinil and caffeine on night-time vigilance of air force crewmembers: A randomized controlled trial

Abstract: Background: Fatigue remains an important factor in major aviation accidents. Stimulants may counteract fatigue’s adverse effects, with modafinil as a promising alternative to caffeine. However, the effect of a single dose of modafinil after a limited period of sleep deprivation remains unknown. Aims: This study aims to determine the effect of 200 mg modafinil on vigilance during a limited period of sleep deprivation compared to 300 mg caffeine and placebo. Methods: Thirty-two volunteers of the Royal Netherland… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 40 publications
(47 reference statements)
0
7
0
1
Order By: Relevance
“…This study is part of a larger randomized controlled trial, for an elaborate description of the materials and methods we therefore also refer to Wingelaar-Jagt et al (2023) ( Wingelaar-Jagt et al, 2023 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This study is part of a larger randomized controlled trial, for an elaborate description of the materials and methods we therefore also refer to Wingelaar-Jagt et al (2023) ( Wingelaar-Jagt et al, 2023 ).…”
Section: Methodsmentioning
confidence: 99%
“…According to the design protocol of the study, their test results were included in the analysis. The subjects characteristics are equal to those described in the article about the comparison between the effects of modafinil and caffeine with placebo on night-time vigilance ( Wingelaar-Jagt et al, 2023 ): Subjects’ ages ranged from 25 to 59 years (median age: 30.9 years, IQR: 28.9–39.3 years). Among the 32 subjects, five (16%) were female, and a majority of 21 (66%) were pilots.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ademais, a cafeína pode efetuar uma função muito importante e necessária na aviação militar, em particular em ocorrências em que os pilotos já estão adinâmicos, mas ainda há necessidade operacional de continuidade de sua missão (Wingelaar-Jagt et al, 2023).…”
Section: Introductionunclassified
“…Recently, an interesting article was published in Journal of Psychopharmacology in which the effects of modafinil and caffeine on the night-time vigilance of air force crewmembers who had limited sleep (Wingelaar-Jagt et al, 2023). The study found that both 200 mg modafinil and 300 mg caffeine significantly increase attentiveness during a prolonged period of continuous awake, including the early morning hours when people are least aware, as compared to placebo.…”
mentioning
confidence: 99%